Art and future : energy, climate, cultures - Stupples, Peter (Cambridge Scholars Publishing, 2018)
"This selection of essays examines the future of art in a changing world. In particular, contributors discuss the agency of art in conditions of ecological threats to the natural world, to climate change and the effects of globalisation, neoliberal economics and mass tourism. Following the lead of Chicago-based Frances Whitehead, whose essay is a key text, some contributors take positions on working with local government agencies to embed art-thinking within development projects, going back to the art-thinking at the centre of Kazimir Malevichs work in Vitebsk one hundred years ago in Russia. Other papers highlight small-scale art interventions that bring ecological issues to public notice and suggest positive responses, whilst others discuss large-scale problems brought about by the social, economic and laissez-faire history of the emerging Anthropocene with possible dystopic outcomes"--Amazon.com